The outcomes of intensified 5-fluorouracil plus leucovorin chemotherapy for preoperative chemoradiation in rectal cancers - Neul Ha; Kwang-Dae Hong; Woong Bae Ji; Jung Sik Kim; Jun Won Um (Korean Journal of Clinical Oncology, 2017)
Purpose The clinical benefit of intensified neoadjuvant chemoradiotherapy (CRT) in rectal cancer has not been proved. We investigated clinical outcomes of intensified 5-fluorouracil plus leucovorin (5-FU/LV) chemotherapy. Methods We retrospectively analyzed 45 patients with locally advanced rectal adenocarcinoma who underwent neoadjuvant CRT between 2010 and 2015. Intensified group took additional 1 cycle of 5-FU/LV chemotherapy after radiation completion (resting period) before surgery, compared to conventional group. Results Eighteen patients were in conventional group and 27 were in intensified group. Median follow-up duration was 33.7 months (range, 7.8–75.6 months). Complete response rate was 11.4% (5/45). Twelve patients in conventional group and 16 patients in intensified group achieved downstaging (P=0.435). In aspect of toxicity, anemia and thrombocytopenia tended to be more frequent in intensified group without statistical difference. There was also no difference in survival between two groups. Conclusion The intensified CRT with additional 1 cycle of 5-FU/LV in rectal cancer revealed no clinical benefit compared to conventional regimen. Considering that the adverse event was minimal and generally acceptable, further research with additional cycles of 5-FU/LV is needed to prove a real benefit of intensified CRT.